The Effect of Prangos Ferulacea L on the Haematologic Indices of Diabetic Rats - Saeedeh Hojabrian; padideh Ebadi; Mokhtar Mokhtari (Journal of Advanced Biomedical Sciences, 2015)
Background & Objective: Diabetes mellitus is a heterogenic metabolic disease in which hyperglycemia leads to glycosylation of RBC membrane and damage of bone marrow stem cells. Because of high flavonoid content of Prangos Ferulacea lindl, the effects of its aqueous- alcoholic extracts on hematologic incidences of diabetic male rats have been studied.